2013
DOI: 10.1371/journal.pone.0073443
|View full text |Cite|
|
Sign up to set email alerts
|

First Report of Circulating MicroRNAs in Tumour Necrosis Factor Receptor-Associated Periodic Syndrome (TRAPS)

Abstract: Tumor necrosis factor-receptor associated periodic syndrome (TRAPS) is a rare autosomal dominant autoinflammatory disorder characterized by recurrent episodes of long-lasting fever and inflammation in different regions of the body, such as the musculo-skeletal system, skin, gastrointestinal tract, serosal membranes and eye. Our aims were to evaluate circulating microRNAs (miRNAs) levels in patients with TRAPS, in comparison to controls without inflammatory diseases, and to correlate their levels with parameter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 43 publications
0
23
0
1
Order By: Relevance
“…Recent studies have shown that plasma expression of miRNAs is altered in various autoimmune and autoinflammatory diseases, and miRNAs may also have effects in the pathogenesis of these diseases. 2,5,6,10 In this study, we aimed to analyze the plasma expression of some candidate miRNAs associated with the pathogenesis of autoimmunity and inflammation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies have shown that plasma expression of miRNAs is altered in various autoimmune and autoinflammatory diseases, and miRNAs may also have effects in the pathogenesis of these diseases. 2,5,6,10 In this study, we aimed to analyze the plasma expression of some candidate miRNAs associated with the pathogenesis of autoimmunity and inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, miRNAs may have a role in the pathogenesis of inflammation and be useful in diagnosis and follow-up of these diseases. [6][7][8][9][10] It has been shown in different studies that miRNA-155 has immunomodulatory functions and miRNA-155 levels were elevated in the macrophages of synovial fluid of patients with chronic arthritis. [11][12][13] The impacts of miRNA-155 in the physiological function of the immune system have also been shown.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the varied presentations, a unifying presentation in TRAPS patients is the elevated levels of serum TNF, IL-1β and IL-6 cytokines. TRAPS treatment options vary but broad immunosuppression, such as with colchicine, is no longer generally recommended, as it is accepted that there is significant benefit in treating patients only at the times of inflammation, that is, during disease flares, and potentially monitored via levels of serum S100 proteins, IL-18, serum amyloid A, and even miRNA molecules [61,62]. With the number of inflammatory cytokines that are elevated, the treatment options range from generic immune suppressants (e.g.…”
Section: Inflammatory Cytokines In Psoriasis (And Psoriatic-type Arthmentioning
confidence: 99%
“…Essi sono coinvolti nei processi di malattia e possono potenzialmente servire come marcatori diagnostici o bersagli terapeutici [10][11][12][13]. La biologia del trascrittoma è estremamente complessa, basti pensare agli effetti dell'epigenetica e dell'epigenomica sulla regolazione della trascrizione o all'intero campo delle modifiche post-traslazionali, sia sulle misure di singoli trascritti genici, sia sulla misura simultanea di migliaia di trascritti.…”
Section: Profilo DI Espressione Genicaunclassified